2015
DOI: 10.1080/15548627.2015.1009778
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5 regulation of ammonia-induced autophagy and mitophagy

Abstract: In liver the mitochondrial sirtuin, SIRT5, controls ammonia detoxification by regulating CPS1, the first enzyme of the urea cycle. However, while SIRT5 is ubiquitously expressed, urea cycle and CPS1 are only present in the liver and, to a minor extent, in the kidney. To address the possibility that SIRT5 is involved in ammonia production also in nonliver cells, clones of human breast cancer cell lines MDA-MB-231 and mouse myoblast C2C12, overexpressing or silenced for SIRT5 were produced. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
207
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(235 citation statements)
references
References 75 publications
6
207
2
1
Order By: Relevance
“…Sebastian et al showed that SirT6 represses MYC, and, by extension, the expression of GLS [112]. A more direct interaction was demonstrated by Poletta and colleagues, who used immunoprecipitation assays to show that GLS binds directly to SirT5 [113]. They additionally showed that GLS was succinylated in the absence of SirT5, and suggested that the de succinylation activity of SirT5 acted to regulate GLS activity.…”
mentioning
confidence: 87%
“…Sebastian et al showed that SirT6 represses MYC, and, by extension, the expression of GLS [112]. A more direct interaction was demonstrated by Poletta and colleagues, who used immunoprecipitation assays to show that GLS binds directly to SirT5 [113]. They additionally showed that GLS was succinylated in the absence of SirT5, and suggested that the de succinylation activity of SirT5 acted to regulate GLS activity.…”
mentioning
confidence: 87%
“…SIRT1-3 have been well studied for decades (Bell and Guarente, 2011;Donmez and Outeiro, 2013;Mellini et al, 2015), whereas SIRT4-7 have received relatively little attention until recently. SIRT5 has become an active topic of research towards its biological and physiological functions (Du et al, 2011;Nishida et al, 2015;Polletta et al, 2015;Tan et al, 2014). Several studies have demonstrated that SIRT5 actually has relatively weak deacetylase activity comparing with other sirtuins.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, SIRT5 has robust desuccinylation, demalonylation and deglutarylation activities in vitro and in vivo, ∼1,000-fold higher catalytic efficiency than deacetylation activity . Many studies also revealed that SIRT5 plays crucial roles in the regulation of ammonia detoxification (Nakagawa et al, 2009;Polletta , 2015), fatty acid oxidation (Park et al, 2013;Zhang et al, 2015), cellular respiration (Li et al, 2015a;Park et al, 2013), ketone body formation (Rardin et al, 2013), and reactive oxygen species (ROS) management , and disregulation or uncontrolled activation of SIRT5 can cause several human diseases, for instance cancer, Alzheimer's disease, and Parkinson's disease (Kumar and Lombard, 2015;Lai et al, 2013;Liu et al, 2015;Lu et al, 2014;Parihar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It targets carbamoyl phosphate synthetase 1 (CPS1), urate oxidase (UOX), and glutaminase (GLS) to regulate the balance of the urea cycle and mitophagy (22)(23)(24)(25). It controls fatty acid oxidation through desuccinylating 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2), enoyl-CoA hydratase a-subunit (ECHA), and demalonylating malonyl-CoA decarboxylase (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%